Introduction to thermal and fluids engineering - Kaminski, Deborah; Jensen, M. K. (Hoboken, N.J. : Wiley, 2005)
'Deborah Kaminski and Michael Jensen present a highly innovative and integrated approach that highlights the interconnections among thermodynamics, fluid mechanics, and heat transfer. The text introduces these three topics early, allowing students to build a firm foundation for later chapters. Throughout the text, integrated examples and problems illustrate the interconnected nature of the three disciplines.'--Jacket.
Introduction to thermal and fluids engineering -- The first law -- Thermal resistances -- Fundamentals of fluid mechanics -- Thermodynamic properties -- Applications of the energy equation to open systems -- Thermodynamic cycles and the second law -- Refrigeration, heat pump, and power cycles -- Internal flows -- External flows -- Conduction heat transfer -- Convection heat transfer -- Heat exchangers -- Radiation heat transfer -- Ideal gas mixtures and combustion (web).
Includes index.
Keywords: Thermodynamics; Heat -- Transmission; Fluid mechanics